THE EXISTENCE OF GOD IN A DOGMATIC APPROACH - Zaprulkhan, Zaprulkhan (Scientia: Jurnal Hasil Penelitian, 2019)
In the perspective of religious history, humans are not only homo sapiens, rational thinking beings, but also homo religiosus, religious beings who always depend on and worship God. As homo religiosus, humans always try to find meaning in their lives by connecting it to the ultimate reality which he calls God. The search for meaning is what drives humans to always build their perspectives, conceptions and religious experiences about God. In the view of some experts, the initial construction built by humans religiously is through their perception of God. Man's perception of God that is packaged and taught in that religion, is indeed built on the basis of God's revelation, so as to obtain a dogmatically solid foundation. This paper will discuss the existence of God which is sourced from revelations namely the Qur'an dogmatically.